A COMPREHENSIVE STUDY FOR THE IDENTIFICATION OF DIABETES MELLITUS TYPE 1 IN INDONESIA (ACROSS 21 STUDY PRELIMINARY REPORT) - Panusunan, Roy; Koharudin, Leonardus; Wijaya, Indra; Harahap, Alida; Suryaatmadja, Marzuki (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Testing for islet cell autoantibody markers such as anti- GAD65, anti-IA2, anti-ZnT8, or IAA, for diagnosing diabetes mellitus type 1 (T1 DM) from other types of diabetes is underutilized in Indonesia. Comprehensive study of identifying T1 DM, involving the measurements of fasting sugar, HbA1c, glycated albumin, C-peptide, and 3 islet cell autoantibody markers: anti-GAD65, anti-IA2, and anti-ZnT8. METHODOLOGY Of 43 samples examined, 18 were classified as normal while 25 fulfilled the standard criteria for diabetes mellitus. RESULTS One out of 18 normal sugar samples and 9 out of 25 diabetic samples were found to have low C-peptide level. Evaluation using a combination of the 3 islet cell autoantibodies used in this study revealed 5 out of the 16 diabetic samples having measurable level of 1 or 2 autoantibodies. Two out of the 17 normal sugar samples with normal C-peptide level demonstrated measurable level of at least 1 autoantibody marker. Out of the 10 samples with low C-peptide level, only 5 samples demonstrated measurable level of 1 or 2 autoantibodies. CONCLUSION Islet cell autoantibodies could be present in normal sugar samples with normal C-peptide level. A low C-peptide does not automatically translate to the presence of islet cell autoantibodies. Measurement of islet cell autoantibody markers for a precise diagnosis of T1 DM in Indonesia is important.